The effect of spray solution storage time on nicosulfuron efficacy applied in Urochloa brizantha cv. Marandu (Research, Society and Development, 2020)
Nicosulfuron is the commonly used herbicide for the control of annual weeds and broadleaf weed species in maize production. However, little is known about the length of time nicosulfuron can remain in the spray tank prior to application in the field without impacting efficacy. The objective of this study was to evaluate the effect of different storage times of the nicosulfuron spray solution on phytotoxicity, production and physiology of Marandu palisadegrass [Urochloa brizantha (Hochst. ex A. Rich.) R. D. Webster cv. Marandu]. The experiment was analyzed in a 6 × 5 factorial arrangement with a complete randomized design. The treatments were six storage times of the nicosulfuron spray solution (0, 6, 12, 24, 48 and 72 h) applied in the Marandu palisadegrass, and five evaluation periods (0, 7, 14, 21 and 60 days after application). Phytotoxicity by the nicosulfuron in the Marandu palisadegrass had parabolic pattern as a function of the interaction between storage time and evaluation period. The photosynthetic rate decreased as a function of the days after nicosulfuron application and showed a discrete increase as a function of the spray solution storage time. Nicosulfuron solution acidifies with time and the effects on phytotoxicity decreased by 30% after 72 h.